Social Networking in Higher Education: Perceptions of Teachers and Learners - Taskiran, Ayse (American Journal of Social Sciences and Humanities, 2019)
English language has become one of the most popular international languages that has been most widely taught, learnt, and used by millions of people. Therefore, many higher education institutions in Turkey provide compulsory English language education, but the students are less likely to get chances to practice the language outside the classroom. Language teachers also find it as a challenge to get their students to practice the language after school. To be able to cope with this challenge, social networks, such as Edmodo, which is a social network created for educational purposes, offer promising alternative social spaces that support social interaction and enhance fast and easy information exchange. Constructed in a mixed methods research design, this study, including teachers and students as both stakeholders, aimed to obtain in-depth data on the perceptions of Edmodo use in language classes. The survey given to the learners and interviews conducted with the teachers revealed similar positive perceptions regarding Edmodo. According to majority of the participants, networks like Edmodo provide opportunities for life-long learning, international collaboration, practical assessment, time and space independent communication, and easy performance monitoring.